Coesão e coerência: uma análise da produção escrita de alunos surdos do 3º ano do Ensino Médio regular da Escola Luiz Nunes Direito - PEREIRA, Márcia Fernanda Falcão (2019)
This article presents a case study involving three deaf students of the 3rd year of high school, from the school "Luiz Nunes Direito", located in Conjunto Cidade Nova VI in the town of Ananindeua in the state of Pará, in which we had analyzed the meaning production process in the texts of deaf students by observing two main aspects: (1) cohesion; and (2) coherence. The process of textual deaf organization was investigated in authors like BENTES (2003); BROCHADO (2003); KOCH (1997); and SALLES et. al. (2004), which provide the necessary theoretical basis for understanding the meanings of production process in the texts of deaf students, more specifically, with regard to cohesion and coherence. From the analysis of the texts of deaf students involved in this research, we realized that although the cohesion be affected, coherence remains unchanged.